Proceedings of the International Symposium for Production Research 2018 - Durakbasa, Numan M.; Gencyilmaz, M. Günes; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The conference aims at forming a unique platform to bring together academicians and practitioners from industrial engineering and management engineering as well as from other disciplines working on production function applying the tools of operational research and production/operational management. Topics treated include: computer aided manufacturing, industry 4.0, big data and analytics, flexible manufacturing systems, fuzzy logic, industrial applications, information technologies in production management, optimization, production economy, production planning and control, productivity and performance management, project management, quality management, risk analysis and management, supply chain management.
RSM and Neural Network Modeling of Surface Roughness During Turning Hard Steel -- A Data Mining Approach to Predict E-Commerce Customer Behaviour -- Data Mining in Digital Marketing -- A Multimoora Method Application With Einstein Interval Valued Fuzzy Numbers' Operator -- Analysis of the Impact of Ball Bearing Track Waviness on their Frictional Moment -- Application of Wavelet Transform to Determine Surface Texture Constituents.
Keywords: Industrial engineering; Production engineering; Industrial and Production Engineering